"It's just a cross, don't shoot": white Supremacy and Christonormativity in a small midwestern town - Eleanor, Kate, author; Souza, Caridad, advisor; Bubar, Roe, advisor; Daum, Courtenay, committee member (Colorado State University. Libraries, 2017)
This paper, guided by poststructuralist and feminist theories, examines public discourse that emerged in response to a controversy over whether a large cross should be removed from public property in a highly visible location in Grand Haven, Michigan. Situating the controversy within the context of the election of U.S. President Donald J. Trump, this thesis seeks to answer the inquiry: How do the events and discourse surrounding the controversy over a cross on public property in a small, Midwestern city shed light on the Trump phenomenon? A qualitative study using document data was conducted, using grounded theory method to analyze 152 documents obtained from publically accessible sites on the internet. Three conceptual frameworks, Whiteness, Christian hegemony, and spatiality were utilized in evaluating the data. Findings reveal a community that sits at the intersection of White and Christian privileges. So interconnected are these privileges that they create a system of "codominance," in which they cannot be conceptually separated from one another, and together constitute the necessary criteria for full inclusion in the community. This qualitative study paints a compelling picture of the ways in which racial and religious privilege affect the underlying belief systems of many members of an overwhelmingly White, Christian community. Results provide valuable insight into the mindset of a Trump supporting community in the period immediately preceding the 2016 election.